2000
DOI: 10.1046/j.1471-4159.2000.0741773.x
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of Rat Parkin cDNA and Distribution of Parkin in Rat Brain

Abstract: Abstract:The rat parkin cDNA sequence was characterized after screening a rat hypothalamus cDNA library with a 32 Plabeled probe containing the entire open reading frame of the human parkin cDNA. This sequence encompasses 1,576 bp and contains a single open reading frame that encodes a 465-amino acid protein. The rat parkin amino acid sequence exhibits a very striking homology to the human and mouse parkin, with 85 and 95% identity, respectively. Both the N-terminal ubiquitin and the ring-IBR (in between ring)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…Expression studies in mammals demonstrated that, in addition to brain regions, parkin is expressed widely in extracerebral tissues 16,17 and the fact that parkin mRNA is expressed in the bovine PNS 18 supports the contention that this protein also plays a role in the PNS. In bovine peripheral nerve, parkin protein was shown recently to be present at two distinct locations: the axoplasm of the myelinated nerve fibers, and the Schwann cells.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Expression studies in mammals demonstrated that, in addition to brain regions, parkin is expressed widely in extracerebral tissues 16,17 and the fact that parkin mRNA is expressed in the bovine PNS 18 supports the contention that this protein also plays a role in the PNS. In bovine peripheral nerve, parkin protein was shown recently to be present at two distinct locations: the axoplasm of the myelinated nerve fibers, and the Schwann cells.…”
Section: Discussionmentioning
confidence: 89%
“…After first-strand cDNA synthesis, the parkin cDNA was co-amplified together with the glyceraldehyde-3-phosphate dehydrogenase (G3PDH) cDNA as an endogenous standard sequence. 17 Two regions of the parkin cDNA were amplified: a first set of primers (forward 5Ј-TTCAACTCCAGCCATGGTTTC-3Ј and reverse 5Ј-CG-TAATGCAAGTGATGTTCCG-3Ј) was designed to span parkin exons 2 to 6 (120 -821 base pairs [bp] of cDNA GenBank accession number AB009973). A second primer set (forward 5Ј-TTAAATGTGGAGCACACCCCA-3Ј and reverse 5Ј-TTT-GGAGGCTGCTTCCCAA-3Ј) was used to amplify parkin exons 6 to 11 (729 -1,325 bp of cDNA, GenBank accession number AB009973).…”
Section: Molecular Analysismentioning
confidence: 99%
“…These findings are similar to the localization of endogenous Parkin reported by others. Although the majority of staining is cytoplasmic (Shimura et al, 1999;Gu et al, 2000;Horowitz et al, 2001), nuclear (Stichel et al, Parkin Inclusion Formation Vol. 14, November 2003 2000; Horowitz et al, 2001), ER (Imai et al, 2002), Golgi (Shimura et al, 1999), trans-Golgi network, and vesicular staining (Kubo et al, 2001) have also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…GST⅐NR2B was a gift from Dr. David Bredt (UCSF). The parkin antibody ASP5p was described previously (15). The anti-Ubl parkin antibody was raised in rabbit against the GST⅐Ubl fusion protein.…”
Section: Methodsmentioning
confidence: 99%